Analisis butir dan level kognitif pada soal penilaian tengah semester gasal mata pelajaran bahasa indonesia kelas iv sekolah dasar - Shafa Nur Rohma; Rukayah Rukayah; Supianto Supianto (Didaktika Dwija Indria, 2023)
Abstract. This study aims to determine the validity, reliability, difficulty index, discriminator index, distractor efficiency, and distribution of cognitive levels in the odd mid-semester assessment items for the Indonesian language class IV SDN Bratan 1 in the 2022/2023 academic year.  This study uses a quantitative approach to descriptive methods with documentation study data collection techniques.  Based on the study results, it was concluded that the question documents analyzed had a content validity level of 0.8333 – 1. Based on item validity, the results obtained were 35% valid and 65% invalid.  Based on reliability, the question has a reliability of 0.55.  Based on the difficulty index, the results obtained were 65% easy, 35% moderate, and no difficult questions.  Based on the discriminatory index, the results obtained were 5% of bad items, 30% of bad, sufficient, and good items respectively, and 5% of very good items.  Based on the distractor efficiency, there are 15% very bad questions, 20% bad questions, 30% of bad and good questions, and 5% very good questions.  Based on the cognitive level, there are 100% LOTS questions and no HOTS question.